АХБОРОТ ВА ТЕЛЕКОММУНИКАЦИОН ВОСИТАЛАР ЁРДАМИДА ТАЛАБАЛАРДА ПЕДАГОГИК ҲУРФИКРЛИЛИКНИ ШАКЛЛАНТИРИШ - Юнусов, Д.Р. (SCIENCE and SOCIETY, 2020)
In the article the author discusses the use of information and telecommunications, the importance of radical changes in science and technology and the implementation of an integrative approach to the education and upbringing of students' free thinking.
Keywords: reform; information; telekommunication; education; upbringing; formation; personality; information-educational environment; integration; high spirituality